Association Between BDNF Gene Variant Rs6265 and the Severity of Depression in Antidepressant Treatment-Free Depressed Patients - Losenkov, Innokentiy S.; Mulder, Nathaniël J. V.; Levchuk, Lyudmila A.; Vyalova, Natalya M.; Loonen, Anton J. M.; Bosker, Fokko J.; Simutkin, German G.; Boiko, Anastasiia S.; Bokhan, Nikolay A.; Wilffert, Bob; Hak, Eelko; Schmidt, Amand F.; et al. (Frontiers in Psychiatry, 2020)
Background: Brain-derived neurotrophic factor (BDNF) plays an important role in neuronal plasticity, and its dysregulation has been associated with the pathogenesis of mood and anxiety disorders. Prolactin (PRL) is a pituitary hormone which is also produced as a cytokine by immune cells and could be a neurotrophic factor regulating the functional activity of stress-related mechanisms. Aim: to investigate the possible relationship between depressive state and BDNF and PRL genotypes or levels with special reference to severity of depression. Methods: Participants of 18-70 years with a clinical diagnosis of depressive disorder of at least moderate severity were included. These patients had not been treated with antidepressant drugs before admission to hospital during the preceding period of the last 6 months, and 54,5% had never been treated with antidepressant drugs during their entire life. The DNA was genotyped for rs1341239 within the prolactin and for rs6265, rs7124442 and rs11030104 within the BDNF gene. Rs11030104 violated the Hardy-Weinberg equilibrium distribution and was excluded from further analyses. Genetic associations were determined by sequentially regressing prolactin, BDNF, 17-items Hamilton’s Depression (HAMD-17) and Clinical Global Impression scale, Severity (CGI-S) ratings, and depression (absent/present) on the available SNPs. Genetic associations were evaluated assuming an additive model. Results: A total of 186 depressed patients (of which 169 were women) and 94 healthy controls (67 women) were genotyped. After excluding subjects without genetic information on the 3 study SNPs, 217 remained of whom 138 suffered from depression. Within depressed patients we observed an association of rs6265 with HAMD-17: mean difference (MD) 2.33 (95%CI 0.49; 4.16; p = 0.014) and CGI-S: MD 0.38 (95%CI 0.09; 0.66; p = 0.011). No significant association was observed between the prolactin SNP rs1341239 and prolactin levels. Similarly the mean differences of BDNF SNPs did not show an association with BDNF: rs6265 -0.042 ln(pg/ml) (95%CI -0.198; 0.113), and rs7124442 0.006 ln(pg/ml) (95%CI -0.117; 0.130). No other association reached statistical significance. Conclusion: We observed a significant association between BDNF gene variant rs6265 and the severity of depression in newly admitted, antidepressant drug-naïve, depressed patients. Actual PRL and BDNF levels were not associated with the studied genotypes.